Analisis Pengaruh Motivasi Pelatihan, Pengembangan Karir Persepsian dari Pelatihan, dan Intensi Berperilaku dalam Pelatihan terhadap Kepribadian Proaktif dengan Usia sebagai Variabel Pemoderasi - , TURASIH, Sari Sitalaksmi, M.Mgt., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The role of teachers greatly influences the advance of the education, as they should receive more attention from all parties to achieve qualified education. The study is intended to test empirically the effect of training motivation, perceived career development from training, and training behavioral intentions to the proactive personality which is moderated by age. The data collection using questionnaires with a simple random sampling method were given to the elementary school teachers at the Dinas Pendidikan dan Kebudayaan, Purworejo Regency, in Central Java. The empirical analysis was done by using the Moderated Regression Analysis (MRA). The results of the study showed that statistically overall independent variables (training motivation, perceived career development from training, training behavioral intentions) gave significant influence to the proactive personality. In addition, its also showed that age moderated the relationship between the two independent variables, they were training motivation and perceived career development from training to dependent variable (proactive personality). Meanwhile, the age didnât moderate the relationship between training behavioral intentions to proactive personality. The results also showed that the older the age of a teacher caused a positive influence to proactive personality with training motivation and perceived career development from training. Keywords: Training motivation, Perceived career development from training, Training behavioral intentions, Proactive personality, Age, and Moderated Regression Analysis (MRA).